PENGARUH SUKU BUNGA, JUMLAH UANG BEREDAR, KURS, DAN PENGELUARAN PEMERINTAH TERHADAP INFLASI DI INDONESIA - Raihan Rasyidin Akhyar; Novi Khoiriawati; Lathifatul Hidayah; Binti Isnawatul Malikah; Isna Lailia Nur Rohmah (WORLDVIEW ( Development economic and sharia studies journal ), 2024)
Inflation is one of the effects of a prolonged economic crisis that can hit a country. Inflation is a process of rising prices of goods and services in a country that takes place continuously in a long or sustainable period of time. Inflation is caused by an imbalance between the availability of goods and money. This study aims to analyze the effect of interest rates, money supply, exchange rates, and government spending on inflation in Indonesia with a range of years 2017-2022 using 72 samples. In this study using quantitative research methods, and analyzed using multiple linear regression tests and classical assumption tests using IBM SPSS Statistics 25. The results showed that interest rates have a positive effect on inflation, money supply has a negative effect on inflation, exchange rates have no effect on inflation, and government spending has a positive effect on inflation. Simultaneously the four variables affect the inflation rate in Indonesia.